Clustering Analysis of the Population in Db_SHADE Algorithm - Viktorin, Adam; Senkerik, Roman; Pluhacek, Michal; Kadavy, Tomas (Institute of Automation and Computer Science, Brno University of Technology, 2018)
This paper provides an analysis of the population clustering in a novel Success-History based Adaptive Differential Evolution algorithm with Distance based adaptation (Db_SHADE) in order to analyze the exploration and exploitation abilities of the algorithm. The comparison with the original SHADE algorithm is performed on the CEC2015 benchmark set in two dimensional settings (10D and 30D). The clustering analysis helps to answer the question about prolonged exploration phase of the Db_SHADE algorithm. Possible future research directions are drawn in the discussion and conclusion.
Keywords: Distance based parameter adaptation; SHADE; Differential evolution; DBSCAN